2021
DOI: 10.4103/jmu.jmu_135_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three ultrasound views for internal jugular venous cannulation in patients undergoing cardiac surgery: A randomized trial

Abstract: Background: The quality of needle visualization during ultrasound-guided internal jugular vein (IJV) cannulation determines the ease of procedure, whereas posterior IJV wall puncture is the most common risk associated. The IJV can be imaged in different views, which offer certain advantages over each other. We compared three different ultrasound views for IJV cannulation short axis (SAX), long axis (LAX), and oblique axis (OAX) with respect to the quality of needle visualization, first pass succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…consistent with previous studies [25,31,32]. Notably, our study introduced a stricter metric, the first needle pass without PVWP, not reported previously.…”
Section: Plos Onesupporting
confidence: 92%
See 3 more Smart Citations
“…consistent with previous studies [25,31,32]. Notably, our study introduced a stricter metric, the first needle pass without PVWP, not reported previously.…”
Section: Plos Onesupporting
confidence: 92%
“…In our study, OA-IP approach exhibited a higher incidence of PVWP compared to prior studies [25,31,32]. This divergence might be attributed to previous studies not assessing or considering PVWP as a complication, despite evidence suggesting its high incidence and potential impact on patient outcomes [12,30,33,34].…”
Section: Plos Onecontrasting
confidence: 63%
See 2 more Smart Citations
“…Cannulation of the IJV is performed for administering medications, fluids, and monitoring pressures, and in cardiac surgery patients for hemodynamic monitoring and measuring cardiac filling pressures [27,115]. The goal is to have a successful first attempt at cannulation because increased attempts increase the risk of complications [115].…”
Section: Internal Jugular Vein Cannulationmentioning
confidence: 99%